Adaptive algorithm for estimating power frequency phasors using dynamic window length. Issue 14 (1st November 2016) - Yang, Liming; Jiao, Zaibin; Kang, Xiaoning; Song, Guobing; Suonan, Jiale
Abstract : Estimating phasors as quickly as possible while guaranteeing accuracy is important to ensure reliable fault detection and isolation in power systems. Window length is an important factor for phasor estimation. The conventional fixed window length cannot handle well the many and diverse fault voltage and current signals. By analysing the relationship between accuracy and window length of a phasor estimation using the matrix pencil method, a criterion is established to determine whether or not the estimated phasor is credible. Then, an adaptive algorithm to estimate the phasors using dynamic window length is proposed. Analytical and experimental investigations show that the proposed algorithm can accurately and timely estimate phasors and can enable reliable and quick relay operation.